Bulbophyllum chyrmangensis (Orchidaceae: Epidendroideae), a new species from Meghalaya, Northeast IndiaBulbophyllum chyrmangensis (Orchidaceae: Epidendroideae), a new species from Meghalaya, Northeast India - Verma, Durgesh; Lavania, Seshu; Singh, Sushil Kumar (Phytotaxa, 2015)
Bulbophyllum section Brachyantha (Reichenbach 1861: 264) comprises about 26 species distributed from India to Japan and the Philippines, with one species in New Guinea (Vermeulen 2014: 27). In northeastern India, the section is represented by nine species (Hooker 1890, Augustine et al. 2001, Lucksom 2007, Rao 2007, Chen & Vermeulen 2009), which were earlier treated under Bulbophyllum section Umbellata (Bentham & Hooker 1883: 503).